Land cover dynamics and their driving factors in a protected floodplain ecosystem - Basumatary, Himolin; Devi, Haobam Suchitra; Borah, Suranjana Bhaswati; Das, Apurba Kumar (Wiley, 2021)
Floodplains are simultaneously the most productive and threatened ecosystems in the world, with land cover integrity compromised even in “protected” floodplains. Due to their rich biodiversity, monitoring of land cover and understanding the causative drivers becomes imperative in the protected floodplains. This work performs spatio‐temporal assessment of land cover changes and discovers the underlying processes in the largest protected floodplain of the Brahmaputra River (BR)—Kaziranga National Park (KNP). Remotely sensed images of 1988, 1998, 2008, and 2018 were analyzed using visual interpretation techniques coupled with class description keys in GIS platform along with ground‐based surveys. Results show a substantial area decline under Dense Forest (7.7%), Open Forest (10%), Waterlogged wetland (31.3%), and Marsh/Swamp (70.4%) land cover classes between 1988 and 2018. The considerable reduction in forests and wetlands is likely to impact the life support system of the park as they form the key habitats and food resources. Concurrently, dramatic area increase under riverine classes has led to huge landmass loss along the northern and eastern stretch. Though the BR and the local flood pulse are essential source of nutrient replenishment in the park, they also act as primary drivers of land cover alteration. Hydro‐geomorphic processes like bank erosion, high‐flood events, and siltation in association with vegetation succession and invasive species control the inter‐conversion of land cover classes in the KNP. The findings of this work provide an insight into the natural factors that instigate the land cover modification on large floodplains in general, and particularly in KNP.